Attitudes to a marine protected area are associated with perceived social impacts - McNeill, A.; Clifton, J.; Harvey, Euan (Pergamon, 2018)
© 2018 Elsevier Ltd Marine protected areas (MPAs) conserve marine biodiversity and ecosystems by limiting or prohibiting resource use in specific areas. Reduced access to a marine resource will invariably impact local communities which reside nearby and utilise those resources. Social dimensions are recognised as crucial to the success of MPAs in meeting environmental goals, however, these dimensions are poorly understood. While much research is focused on developing countries, the majority of recent growth in MPA coverage is occurring in more economically developed settings. This research aims to address this gap by exploring the diversity of social impacts associated with an established MPA on the mid-coast of Western Australia. A range of extractive and non-extractive stakeholders were interviewed to identify the type of impacts experienced and how these are associated with attitudes towards the MPA. The results demonstrate there is a strong association between the nature of the impacts experienced by stakeholders and their attitudes. The social impacts are not distributed uniformly among stakeholders, with some groups of extractive users suffering the majority of the negative impacts and holding highly critical attitudes. The most common adverse impacts affect individual users’ well-being including feelings of fear, stress, uncertainty and inequity, while impacts on fishing activities are limited. Those who reported broader scale community or environmental benefits held largely positive assessments of the MPA. Together these results illustrate the importance of identifying and mitigating the full spectrum of social impacts experienced, as opposed to a narrow focus on the disruption of fishing activities or socio-economic impacts alone.